2022
DOI: 10.1002/jsf2.89
|View full text |Cite
|
Sign up to set email alerts
|

Drought tolerance promoted by complementation of ascorbate‐glutathione system and antioxidant‐rich phytochemicals in Amaranthus hypochondriacus L.

Abstract: Background: Complementation of enzymatic and nonenzymatic antioxidative defense plays a decisive role in redox regulation of crops under drought. However, such type of study in Amaranth, particularly understanding the relationship between drought tolerance through tandem action of enzymatic and non-enzymatic bioactive antioxidants having phytonutrient promise is seldom studied and hence is the objective of the present investigation.Results: A comparative evaluation of dehydration stress-induced changes in reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
1
0
0
Order By: Relevance
“…Although most of the biochemical and enzymatic parameters analyzed in this study were found to change drastically during HS and subsequent recovery, it was nevertheless found that, similar to WDS, greater HS tolerance in A. hypochondriacus compared to the other two grain amaranth species coincided with a number of specific parameters such as: i) a very pronounced depletion of leaf starch reserves during the HS treatment, and ii) a significantly higher accumulation of foliar Pro, Suc, total phenols and flavonoids and betalains and other pigments at the latter stages of the HS treatment. This pattern coincided with the greater accumulation of redox-sensitive phenols and flavonoids recently reported in WDS-tolerant accessions of A. hypochondriacus ( Aditya et al., 2022 ). Likewise, a comparison of thermosensitive and thermotolerant lettuce cultivars revealed that the latter differentially accumulated specific phenylpropanoid and flavonoid compounds known to have strong antioxidant activity, upon heat treatment ( Oh et al., 2009 ; Wei et al., 2021 ).…”
Section: Discussionsupporting
confidence: 87%
“…Although most of the biochemical and enzymatic parameters analyzed in this study were found to change drastically during HS and subsequent recovery, it was nevertheless found that, similar to WDS, greater HS tolerance in A. hypochondriacus compared to the other two grain amaranth species coincided with a number of specific parameters such as: i) a very pronounced depletion of leaf starch reserves during the HS treatment, and ii) a significantly higher accumulation of foliar Pro, Suc, total phenols and flavonoids and betalains and other pigments at the latter stages of the HS treatment. This pattern coincided with the greater accumulation of redox-sensitive phenols and flavonoids recently reported in WDS-tolerant accessions of A. hypochondriacus ( Aditya et al., 2022 ). Likewise, a comparison of thermosensitive and thermotolerant lettuce cultivars revealed that the latter differentially accumulated specific phenylpropanoid and flavonoid compounds known to have strong antioxidant activity, upon heat treatment ( Oh et al., 2009 ; Wei et al., 2021 ).…”
Section: Discussionsupporting
confidence: 87%